Regional Potential for Community Welfare Development in Sodo Village, Gunung Kidul - Idawijayanti, Tri; Suhendro, Suhendro; Sumardiyana, Sumardiyana (Sekolah Tinggi Pertanahan Nasional, 2023)
Sodo Village contains physical and non-physical potential that can be developed, albeit this potential is limited or constrained in actuality. In 2021, 74% of the population in Sodo village were impoverished. The goal of this research is to develop the region's potential through community empowerment programs. This study employed descriptive qualitative research methodologies, including data inventory on prospective physical and non-physical regions, spatial analysis, and problem tree analysis. The following issues arise in the Sodo Village: limited physical potential, ineffective management of MSMEs potential, and tourist potential. Participatory community empowerment initiatives are used to develop regional potential.